Dekomposisi Wavelet Data Seismik Broadband dari Stasiun Wanagama Yogyakarta pada saat Letusan Gunung Merapi 2010: Dairoh, Wiwit Suryanto - Dairoh Dairoh; Wiwit Suryanto Wiwit Suryanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
Eruption of mount Merapi in 2010 has caused damaged the seismic observation stations installed around mount Merapi. This research aimed to investigate the characteristics of Mount Merapi is volcanic earthquakes of the outside of volcanoes danger area(Wanagama station). The analysis was conducted by wavelet decomposition process to separate the noise volcanic and seismic events were recorded during the period of the eruption of Mount Merapi, 2010. The decomposition process was done by using wavelet Daubechies order of 5. The interpretation was made by looking at the characteristics of volcanic seismic signals with frequency content of the signal decomposition. From the results, the research shows event of volcanic earthquakes that occurred during the 2010 eruption of Merapi.